Response of Dryland Sorghum to Sulphur Application - Kalyansundaram, N K; Patil, R G; Patel, G A; Patel, I S (Annals of Arid Zone, 2016)
A field experiment was conducted during kharif seasons from 1989 to 1992 10 study the effect of sulphur on dryland sorghum grown on a Typic Ustipsamments dericient in available S. Three sources of S, viz .. ammonium sulphate (AS). gypsum (OS) and elemental sulphur (ES) were tested at 20. 40. 60 and 80 kg S ha-1 levels along with two controls. A significant fodder yield response to S was obtaincd only when the rainfall distribution was favourablc (895 mm. 41 rainy days) and yield levels were high. Application of 20 kg S ha-1 through gypsum or elemental sulphur. or use of ammonium sulphate toÂ· supply 80 kg ha-1Â , was found advantageous, both from yield and economic points of view.